COMPARISON OF MATHEMATICAL PROBLEM SOLVING ABILITIES BETWEEN HIGH SCHOOL STUDENTS WHOSE LEARNING USES THE CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH AND THE DISCOVERY APPROACH - Narim Aryodi Bintang (IKIP Siliwangi, 2020)
Learning mathematical conventional and monotonous cause students saturated, conditions such need existence innovation so that happen significant changes to success learning mathematics. Wrong one effortfrom facet teacher is with apply various methods and approaches relavan from every principal discussion corresponding with characteristics material in presentation to students. Howdo teachers empower students onthe method teaching interesting mathematical sothat lesson Mathematics not again tobe a boring lesson and load for students in study . And the teacher's task is asfacilitator who must ready facilitate students in study .In implementation author giveaway some instruments from start test early to test end for knowing development and influence from approach under study. So that obtained valid picture is not just like that theoryfrom book . In research this finally author could conclude that in the analysis of the gain data there are difference , because accordingto calculation from data processing using device Mini-tab 16 soft obtained P0.032meaning H o rejected sothat theconclusion thereis difference Ability solving problem mathematics between approach Contextual Teaching And Learning(CTL) and approaches Discovery